A Hepatitis C Educational Needs Assessment of Canadian Healthcare Providers - Reza Naghdi; Karen Seto; Carolyn Klassen; Didi Emokpare; Brian Conway; Melissa Kelley; Eric Yoshida; Hemant A. Shah (Canadian Journal of Gastroenterology and Hepatology)
Background and Aim. Despite advances in the treatment of chronic hepatitis C infection (CHC), it remains a major public health problem in Canada and globally. The knowledge of healthcare providers (HCPs) is critical to improve the care of CHC in Canada. To assess the current knowledge and educational needs of healthcare providers (HCPs) in the area of CHC management a national online survey was conducted. Method. An interprofessional steering committee designed a 29-question survey distributed through various direct and electronic routes. The survey assessed several domains (e.g., participant and practice demographics, access to resources, knowledge of new treatments, and educational preferences). Results. A total of 163 HCPs responded to the survey. All hepatologists and 8% of primary care providers (PCPs) reported involvement in treatment of CHC. Physicians most frequently screened patients who had abnormal liver enzymes, while nurses tended to screen based on lifestyle factors. More than 70% of PCPs were not aware of new medications and their mechanisms. Conclusion. Overall, the needs assessment demonstrated that there was a need for further education, particularly for primary care physicians, to maximize the role that they can play in screening, testing, and treatment of hepatitis C in Canada.